Research on Human Pose Capture Based on the Deep Learning Algorithm - Wenbin Xie; Xueyun Gu; Xiuming Li; Luqi Zheng; Guodong Li; Haisheng Lu; Huakang Li (Journal of Control Science and Engineering)
A method based on the deep learning algorithm is proposed to accurately capture the posture of the human body. It is one of the important means to improve athletes’ competitive level in modern sports to accurately analyze the posture of sports training by technical means. Aiming at the application demand of using artificial intelligence technology to accurately analyze and predict the motion training posture, a motion posture analysis and prediction system based on deep learning is designed in this paper. Based on the Arduino embedded development board and equipped with multiple IMU sensors, the scheme established a system to collect accurate human movement data such as speed and acceleration by using stepper motors and obtained accurate human movement data. The experimental results show that these models have been trained with H3.6 m data sets. The sampling frequency was reduced to 25 Hz, and the joint angles were converted into exponential graphs. When the time window covers approximately 1 660 ms, the loop network will be initialized to 40 frames, equivalent to 1 600 ms. For each action, a separate pretrained recursive model is used. It is proved that the method based on deep learning can reduce the prediction error of fine-tuning specific movements and effectively classify and predict the movements not included in the original training data.